Causal mapping to explore emergence of construction disputes - Tanriverdi, Cenk; Atasoy, Guzide; Dikmen, Irem; Birgonul, M. Talat (Journal of Civil Engineering and Management, 2021)
Disputes, frequently encountered in construction projects, can substantially affect project success, necessitating a clear understanding of how and why disputes occur. Previous studies on disputes mostly yielded exhaustive lists or hierarchies of possible causes of disputes, which can hardly be used to understand how these causes come together to form a dispute. To address this gap, this study provides an alternative approach to understand the underlying causes of disputes, and their relationship within a specific context, using causal map analysis. This study is conducted using causal mapping approach to understand dispute emergence patterns in practice. Initially, a causal map of construction disputes is developed based on literature. The map is altered and verified through an expert workshop, considering projects contracted through FIDIC Yellow Book. The causal representation of the dispute emergence patterns highlights the importance of pre-construction studies, people factor, and contract terms. It is revealed that significant causes are either result of a chain of preceding factors or are triggers for further ones. This finding reinforces that the occurrence of disputes does not only depend on individual causes; rather, these causes combine with a series of other factors for a dispute to occur.